Multiple Campylobacter jejuni proteins affecting the peptidoglycan structure and the degree of helical cell curvature - Frirdich, Emilisa; Vermeulen, Jenny; Biboy, Jacob; Vollmer, Waldemar; Gaynor, Erin C. (Frontiers in Microbiology, 2023)
Campylobacter jejuni is a Gram-negative helical bacterium. Its helical morphology, maintained by the peptidoglycan (PG) layer, plays a key role in its transmission in the environment, colonization, and pathogenic properties. The previously characterized PG hydrolases Pgp1 and Pgp2 are important for generating C. jejuni helical morphology, with deletion mutants being rod-shaped and showing alterations in their PG muropeptide profiles in comparison to the wild type. Homology searches and bioinformatics were used to identify additional gene products involved in C. jejuni morphogenesis: the putative bactofilin 1104 and the M23 peptidase domain-containing proteins 0166, 1105, and 1228. Deletions in the corresponding genes resulted in varying curved rod morphologies with changes in their PG muropeptide profiles. All changes in the mutants complemented except 1104. Overexpression of 1104 and 1105 also resulted in changes in the morphology and in the muropeptide profiles, suggesting that the dose of these two gene products influences these characteristics. The related helical ε-Proteobacterium Helicobacter pylori has characterized homologs of C. jejuni 1104, 1105, and 1228 proteins, yet deletion of the homologous genes in H. pylori had differing effects on H. pylori PG muropeptide profiles and/or morphology compared to the C. jejuni deletion mutants. It is therefore apparent that even related organisms with similar morphologies and homologous proteins can have diverse PG biosynthetic pathways, highlighting the importance of studying PG biosynthesis in related organisms.